Questions: Use DeMorgan's Laws to write an equivalent statement in symbolic form. Select the correct choice.
-[(p ∧ q) ∨ r]
(p ∨ q) ∧ -r
(p ∧ q) ∨ r
(p ∨ ∼ q) ∧ ∼ r
(-p ∧ ∼ q) ∨ r
(∼ p ∨ q) ∧ ∼ r
(∼ p ∨ ∼ q) ∧ ∼ r
Submit Question
Transcript text: Use DeMorgan's Laws to write an equivalent statement in symbolic form. Select the correct choice.
\[
-[(p \wedge q) \vee r]
\]
$(p \vee q) \wedge-r$
$(p \wedge q) \vee r$
$(p \vee \sim q) \wedge \sim r$
$(-p \wedge \sim q) \vee r$
$(\sim p \vee q) \wedge \sim r$
$(\sim p \vee \sim q) \wedge \sim r$
Submit Question
Solution
Solution Steps
To apply DeMorgan's Laws, we need to distribute the negation across the logical operators inside the expression. DeMorgan's Laws state that the negation of a conjunction is the disjunction of the negations, and vice versa. Therefore, we will apply these laws to the given expression to find an equivalent statement.
Step 1: Original Expression
The original expression we need to analyze is given by:
\[
-\left[(p \wedge q) \vee r\right]
\]
Step 2: Apply DeMorgan's Laws
Using DeMorgan's Laws, we can rewrite the negation of the disjunction:
\[
-\left[(p \wedge q) \vee r\right] = -r \wedge -(p \wedge q)
\]
Step 3: Further Simplification
Next, we apply DeMorgan's Laws again to the term \(-(p \wedge q)\):
\[
-(p \wedge q) = -p \vee -q
\]
Thus, we can rewrite the expression as:
\[
-\left[(p \wedge q) \vee r\right] = -r \wedge (-p \vee -q)
\]
This can be expressed as:
\[
(-r) \wedge (\sim p \vee \sim q)
\]
Final Answer
The equivalent statement in symbolic form is:
\[
\boxed{(-r) \wedge (\sim p \vee \sim q)}
\]